Braille smart glove / Nur Ainul Nabihah Rosli … [et al.] - Rosli, Nur Ainul Nabihah; Mohd Zabidi, Aisyahtul Balqis; Agus, Mursyida; Rashidi, Nur Umairah Najwa; Ahmad Safari, Nursafiza Najwa; Zainal Abidin, Fadhilah (Bahagian Penyelidikan dan Jaringan Industri, UiTM Melaka, 2024)
Braille Smart Glove Nur Ainul Nabihah Binti Rosli, Aisyahtul Balqis Binti Mohd Zabidi, Mursyida Binti Agus, Nur Umairah Najwa Binti Rashidi, Nursafiza Najwa Binti Ahmad Safari, Mrs Fadhilah Binti Zainal Abidin Universiti Teknologi Mara Cawangan Melaka Kampus Bandaraya Melaka. enulbihah@gmail.com Abstract Braille Smart Glove is a product for disabled people and have many functions. One of the most users are from Asian country like Malaysia. As most people know before this, Braille Smart Glove hasn’t been exposed and only book with braille handwriting because of that some people create Braille Smart Glove using various creativity. Braille Smart Glove has been used by blind people and the product has been tested repeatedly to create products with high value. The test results show that the most effective time blind people use this braille glove on keyboard to type something is between 5-10 minutes. That is the best result for the user to save time. Braille Smart Glove is not too thick and comfortable to wear even in hot weather. An advantage of this product will be that blind people to do work and will increase the performance from time to time. Keywords: Smart Glove, Braille, Disable People, Blind